T Cell Receptor Repertoire Analysis Reveals Signatures of T Cell Responses to Human Mycobacterium tuberculosis - Shao, Ming-Ming; Yi, Feng-Shuang; Huang, Zhong-Yin; Peng, Peng; Wu, Feng-Yao; Shi, Huan-Zhong; Zhai, Kan (Frontiers in Microbiology, 2022)
Characterization of T cell receptor (TCR) repertoires is essential for understanding the mechanisms of Mycobacterium tuberculosis (Mtb) infection involving T cell adaptive immunity. The characteristics of TCR sequences and distinctive signatures of T cell subsets in tuberculous patients are still unclear. By combining single-cell TCR sequencing with single-cell RNA sequencing and flow cytometry to characterize T cells in tuberculous pleural effusions (TPEs), we identified 41,718 CD3+ T cells in tuberculous pleural effusions (TPEs) and paired blood samples, including 30,515 CD4+ T cells and 11,203 CD8+ T cells. Compared with controls, no differences in length and profile of length distribution were observed in CDR3 in both CD4+ and CD8+ T cells in TPE. Altered hydrophobicity was demonstrated in CDR3 in CD8+ T cells and a significant imbalance in the TCR usage pattern of T cells with preferential expression of TRBV4-1 in TPE. A significant increase in clonality was observed in TCR repertoires in CD4+ T cells, but not in CD8+ T cells, although both enriched CD4+ and CD8+ T cells showed TH1 and cytotoxic signatures. Furthermore, we identified a new subset of polyfunctional CD4+ T cells with CD1-restricted, TH1, and cytotoxic characteristics, and this subset might provide protective immunity against Mtb.